The existence and stability of onsite solitons in a driven discrete nonlinear nonlocal Schrödinger equation. (May 2020) - Putra, G; Syafwan, M; Haripamyu, H
Abstract: In this paper, we examine numerically the existence and stability of onsite solitons in a driven discrete nonlinear nonlocal Schrödinger equation. The equation interpolates cubic and Ablowitz-Ladik nonlocal equations. We obtain that the solitons are always stable for small interpolation parameter. We also obtain that the driving parametric can destabilize the soliton solution.